Analysis of Audience Reception to the Concept of Masculinity in the ‘Beauty Is Universal’ Campaign - Fawziya Aprelliani; Kezia Arum Sary (PT Mattawang Mediatama Solution, 2023)
Dear Me Beauty, an Indonesian beauty product brand, has become a trending topic of conversation among the public due to the recent of a post. A middle-aged man with Dear Me Beauty's newest product, the Airy Poreless Fluid Foundation. Together with that, Dear Me Beauty has launched a movement entitled ‘Beauty Is Universal’, an effort to invite the public to appreciate all forms of beauty, including various skin colors and genders, with the aim of breaking stereotypes that beauty products only for women. With the People Power Brand claim, Dear Me Beauty is trying to popularize the concept of genderless makeup, where there is no gender constraint regardless of who and what is used. This research was conducted to analyze how audiences interpret the concept of masculinity in the ‘Beauty Is Universal’ campaign conducted by Dear Me Beauty on February 1, 2021, on Instagram. This study used a qualitative approach using Stuart Hall's reception analysis method, which categorized the audiences into three positions: Dominant Hegemonic Position, Negotiated Position, and Oppositional Position. Through utilizing in-depth interviews, this study employed a purposive sampling technique to determine which informants fit the research criteria to examine and understand a person's attitudes and views. The results of this study indicate that audiences have the ability to comprehend and interpret media messages into definitions of life choices and self-identity. Instagram, as a medium, provides a representation of the world that is absorbed and internalized by the audience, internalized, then used to determine decisions and attitudes. Audiences are provided the option to choose which media to consume according to preferences. As a single message cannot be interpreted equally by all audiences, their understanding represents their own decoding of the encoding stage performed by the message producer. The study was found that the dominating informants were in a Dominant Hegemonic Position, indicating their agreement with the ‘Beauty Is Universal’ campaign. These informants believed that Dear Me Beauty successfully conveyed the belief that beauty products were not bound only to a certain gender. The informants’ cultural and religious backgrounds influenced their reception of the campaign’s content.